The Poorhouse : Subsidized Housing in Chicago - Bowly, Devereux, Jr (Book collections on Project MUSE., 2012)
Chicago seems an ideal environment for public housing because of the city's relatively young age among major cities and well-deserved reputation for technology, innovation, and architecture. Yet The Poorhouse: Subsidized Housing in Chicago shows that the city's experience on the whole has been a negative one, raising serious questions about the nature of subsidized housing and whether we should have it and, if so, in what form. Bowly, a native of the city, provides a detailed examination of subsidized housing in the nation's third-largest city. Now in its second editio.